Biocontrol of the causal brown patch pathogen Rhizoctonia solani by Bacillus velezensis GH1-13 and development of a bacterial strain specific detection method - Lee, Gahee; Choi, Hyeongju; Liu, Haifeng; Han, Yun-Hyeong; Paul, Narayan Chandra; Han, Gui Hwan; Kim, Hyunsook; Kim, Pyoung Il; Seo, Sun-Il; Song, Jaekyeong; Sang, Hyunkyu (Frontiers in Plant Science, 2023)
Brown patch caused by the basidiomycete fungus Rhizoctonia solani is an economically important disease of cool-season turfgrasses. In order to manage the disease, different types of fungicides have been applied, but the negative impact of fungicides on the environment continues to rise. In this study, the beneficial bacteria Bacillus velezensis GH1-13 was characterized as a potential biocontrol agent to manage brown patch disease. The strain GH1-13 strongly inhibited the mycelial growth of turf pathogens including different anastomosis groups of R. solani causing brown patch and large patch. R. solani AG2-2(IIIB) hyphae were morphologically changed, and fungal cell death resulted from exposure to the strain GH1-13. In addition, the compatibility of fungicides with the bacterial strain, and the combined application of fungicide azoxystrobin and the strain in brown patch control on creeping bentgrass indicated that the strain could serve as a biocontrol agent. To develop strain-specific detection method, two unique genes from chromosome and plasmid of GH1-13 were found using pan-genome analysis of 364 Bacillus strains. The unique gene from chromosome was successfully detected using both SYBR Green and TaqMan qPCR methods in bacterial DNA or soil DNA samples. This study suggests that application of GH1-13 offers an environmentally friendly approach via reducing fungicide application rates. Furthermore, the developed pipeline of strain-specific detection method could be a useful tool for detecting and studying the dynamics of specific biocontrol agents.